A Novel Concept of High-Voltage Balancing on Series-Connected Transistors for Use in High-Speed Instrumentation - Alexandr Despotuli; Viacheslav Kazmiruk; Anastasia Despotuli; Alexandra Andreeva (Energies)
The novel concept of reliable voltage balancing on N fast high-voltage (HV) transistors, connected in series, is verified by computer modeling/experimental testing. The essence of the concept is to transfer the balancing function from conventional snubbers, resistive dividers, varistors, etc., or sophisticated gate-side control techniques, to “individual” resistive loads (of transistors) connected to “individual” HV sources of power. The concept has been implemented in the recently patented architecture of HV rectangular pulse generators. The operation of any series-connected stack requires (1) synchronization of control actions on gates of all N transistors; (2) static HV balancing on all transistors in OFF states; and (3) dynamic HV balancing during ON↔OFF transients. The goals of the new design are to achieve an exceptionally high level of HV balancing in modes (2) and (3), as well as to simplify the process of configuring/customizing the circuit. Testing confirms that new generators exhibit minimal ripple during ON→OFF transients. Reliable operation with high-quality rectangular pulses is ensured even at a voltage slew rate of more than 100 kV/µs, while each transistor blocks a voltage close to the maximum value specified in its datasheet. The presented novelties are likely suitable for high-speed instrumentation.